EKPLORASI CONTINUANCE INTENTION PADA EXPECTATION CONFIRMATION MODEL BERKELANJUTAN PENGGUNA BUY-NOW-PAY-LATER DI KOTA SEMARANG - Ningrum, Shintia Nabila; Kusuma, Pradana Jati; Safitri, Maria; Prawitasari, Dian (Distribusi - Journal of Management and Business, 2026)
This study examines the effects of financial literacy, perceived usefulness, and perceived risk on continuance intention in the use of PayLater services by considering satisfaction as a mediating variable and confirmation as a moderating variable among PayLater users in Semarang City, within the framework of the Expectation Confirmation Theory (ECT) and Technology Acceptance Model (TAM). This research adopts a quantitative approach with an explanatory research design. Data were collected through an online questionnaire from 156 active Buy Now Pay Later (BNPL) users in Semarang City using purposive sampling and were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that financial literacy has a significant effect on continuance intention, while perceived usefulness positively affects continuance intention through satisfaction. User satisfaction emerges as the strongest determinant influencing continuance intention, suggesting that actual usage experience plays a more critical role than initial perceptions. In contrast, perceived risk does not have a significant direct effect on continuance intention. These findings imply that user experience and satisfaction are more influential in sustaining BNPL usage than initial cognitive factors. This study provides practical implications for BNPL service providers to prioritize service quality and system usability. Therefore, providers are encouraged to enhance financial literacy education while strengthening service benefits and quality to improve user satisfaction and promote continued usage, particularly among PayLater users in Semarang City.